1993
DOI: 10.1099/00222615-38-2-151
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of bacterial strains isolated from acute dentoalveolar abscess

Abstract: Summary.The phagocytosis by human polymorphonuclear leucocytes of 37 bacterial strains identified as Streptococcus rnilleri (10 strains), strictly anaerobic gram-positive cocci (10) Prevotella intermedia (6), Pr. oralis ( 5 ) and Fusobacteriurn nucleaturn (6) was investigated in vitro. The ingestion of S. rnilleri and strictly anaerobic gram-positive cocci was significantly greater (p < 0.001) than that of strains of Prevotella spp. and F. nucleaturn. The degree of uptake of capsulate and non-capsulate strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Interestingly, in cases with polymicrobial intra‐amniotic infection, cocci were the most commonly observed microorganisms engulfed by amniotic fluid neutrophils, suggesting that these innate immune cells prefer to engulf this genus. This finding is consistent with a previous report demonstrating that neutrophils favor the ingestion of Gram‐positive cocci over Gram‐negative bacilli . Yet, our ex vivo phagocytosis assays showed that amniotic fluid neutrophils can also phagocytize bacilli.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, in cases with polymicrobial intra‐amniotic infection, cocci were the most commonly observed microorganisms engulfed by amniotic fluid neutrophils, suggesting that these innate immune cells prefer to engulf this genus. This finding is consistent with a previous report demonstrating that neutrophils favor the ingestion of Gram‐positive cocci over Gram‐negative bacilli . Yet, our ex vivo phagocytosis assays showed that amniotic fluid neutrophils can also phagocytize bacilli.…”
Section: Discussionsupporting
confidence: 93%
“…Peripheral blood PMN were less able to phagocytose strains of gram-negative anaerobic rods isolated from acute dentoalveolar abscesses than strains of gram-positive cocci [12]. In our study the negative influence of a leukotoxin-producing strain of A. actinomycetemcomitans on phagocytosis was demonstrated.…”
Section: Discussioncontrasting
confidence: 48%
“…Fn has been shown to be resistant to phagocytosis by PMN, although the mechanism was not identified. 46 Pg and Fn cocultured together or alone with mouse DCs show that Pg is the driving force for whether or not by Fn activates DCs. Although uptake was not assessed, in one study the influence of Pg on Fn was attributed to gingipains 47 In a separate study, Fn extracts have been shown to have a suppressive effect on cell-mediated immunity and phagocyte functions, although no mechanism was not identified.…”
Section: Discussionmentioning
confidence: 95%